METAPHOR OF MODALITY IN “EIGHTY DAYS YELLOW” NOVEL BY VINA JACKSON - Mutia, Syuhada (JL3T (Journal of Linguistics, Literature and Language Teaching), 2018)
The purpose of the study to analyze the types of metaphor of modality, describe the realization metaphor of modality and explain the context of metaphor of modality in novel. The research was conducted by applying descriptive qualitative design. The data for this study were the sentences in novel. The data analyzed using Halliday’s Theory. The findings of the study showed that there were three types of the metaphor of modality used in novel such as probability was 50,65% with 109 occurences, usuality was 31,10% with 84 occurences, and obligation 18,25% with 70 occurences, the realization of metaphor of modality in novel were think, will, probably, usually, want, should, expected, usual, and supposed. and the context of metaphor of modality was the social context. We interacted with other people in the social context. Further, the interaction in our surroundings like friends and family. What you speak or how you act to everyone influences how you interprate.